Comparisons of cottonseed meal and mixtures containing urea as nitrogenous (protein) supplements. - Weber, A.D. (Kansas Agricultural Experiment Station, 2012)
Tests with urea in beef cattle rations have been conducted at the Kansas Agricultural Experiment Station since 1940. In the first test, urea was compared with cottonseed meal as a source of nitrogen for fattening calves. The calves were fed individually for 168 days. Basal feeds fed to each group included ground shelled corn, Atlas sorgo silage, cane molasses and a mineral supplement. Both groups received the same quantities of these feeds. In addition, one group received cottonseed meal as a source of nitrogen. A second group received urea and enough other materials to provide the same quantities of nitrogen, energy and minerals furnished by the cottonseed meal fed to the first group.
Keywords: Beef; Cottonseed meal; Urea; Protein supplements